Lessons learned from concerned significant others: a qualitative analysis on involvement in services for young adult opioid use disorder - Nicole P. Porter; Sean Dunnsue; Cori Hammond; Molly Bobek; Alexandra MacLean; Mari Watkins; Craig E. Henderson; Aaron Hogue (Frontiers in Public Health)
IntroductionResearch, clinical wisdom, and government policy recommend family involvement in services for young adult (YA) opioid use disorder (OUD) to improve treatment outcomes. Moreover, research suggests YAs believe that family involvement is essential to OUD treatment and prefer greater involvement of their concerned significant others (CSOs), such as family members, romantic partners, and family-of-choice members in their care. Yet, CSOs are not routinely involved in OUD services for YAs. The main aim of this qualitative study is to learn from CSOs and YAs directly about their thoughts, beliefs, attitudes, and experiences with family-involved services.MethodWe used convenience sampling to recruit 10 YAs (ages 24–36 years) who were in treatment for OUD and their CSOs (5 mothers, 2 grandmothers, 2 partners, 1 aunt) from two urban treatment centers. Using semi-structured interview guides, we conducted qualitative interviews with YAs and their CSOs to explore their experiences, feelings, and attitudes toward family involvement in services. Thematic content analysis started with deductive-dominant group consensus coding followed by matrix analysis to analyze themes in the context of CSO-YA dyads.ResultsWe identified five main themes: (1) CSO-YA relationships were resilient and motivated treatment and recovery, (2) CSOs believed in the importance of family involvement in services and experienced personal benefits by participating, (3) CSO involvement occurred on a continuum from facilitating treatment entry to systemic family therapy, (4) YAs identified CSOs who were supportive and encouraging of treatment even in the face of CSO barriers and challenges, and (5) YAs held accurate perceptions of their CSOs' MOUD attitudes and beliefs.DiscussionIn this qualitative study we learned from YAs and CSOs themselves about the individual and relational benefits of family integration in services and replicated findings from previous research highlighting preferences for greater family involvement in OUD services. Clinical implications and recommendations for challenging barriers to relationship-oriented services and recovery planning for OUD are discussed.